The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.iccn.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

“Not being able to talk was horrid”: A descriptive, correlational study of communication during mechanical ventilation

Abstract: Objectives The purpose of this study was to describe the patient experience of communication during mechanical ventilation Research Methodology This descriptive study is a secondary analysis of data collected to study the relationship between sedation and the MV patients' recall of the ICU. Interviews, conducted after extubation, included the Intensive Care Experience Questionnaire. Data were analyzed with Spearman correlation coefficients (rs) and content analysis. Setting Participants were recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 28 publications
(39 reference statements)
4
69
0
7
Order By: Relevance
“…The findings of present study is in line with a study conducted by Happ MB et al 18 who found that the study subjects rated 40% of the communication sessions with nurses as somewhat difficult to extremely difficult with little to no use of assistive communication strategies. Findings of the present study is also in line with the study conducted by Guttormson JL et al 19 on mechanically ventilated study subjects to describe the patient experience of communication during mechanical ventilation. According to this study inability to communicate needs was associated with helplessness.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of present study is in line with a study conducted by Happ MB et al 18 who found that the study subjects rated 40% of the communication sessions with nurses as somewhat difficult to extremely difficult with little to no use of assistive communication strategies. Findings of the present study is also in line with the study conducted by Guttormson JL et al 19 on mechanically ventilated study subjects to describe the patient experience of communication during mechanical ventilation. According to this study inability to communicate needs was associated with helplessness.…”
Section: Discussionsupporting
confidence: 92%
“…This stressful condition is experienced more frequently than expected by nurses in ICUs . Patients describe their experience of difficulty in communication as “being in limbo,” “being disrupted,” “being imprisoned,” and “being trapped.” It has been reported that ineffective communication and loss of voice lead to feelings of anxiety, anger, fear, disappointment, weakness, and helplessness . This negatively affects care satisfaction .…”
Section: Discussionmentioning
confidence: 99%
“…Patients describe their experience of difficulty in communication as “being in limbo,” “being disrupted,” “being imprisoned,” and “being trapped.” It has been reported that ineffective communication and loss of voice lead to feelings of anxiety, anger, fear, disappointment, weakness, and helplessness . This negatively affects care satisfaction . Nurses should create and maintain an effective communication environment with patients and their families in order to improve satisfaction with intensive care and the quality of life as well…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative reports offer important insights from this uniquely vulnerable population including feelings of being trapped and caged, loss of personhood, and loss of control (2,3). Thus, efforts to restore verbal communication represent an important area of patient-centered investigation with the potential to meaningfully improve patient, family, and clinician experiences.…”
mentioning
confidence: 99%